Health Telematics Education - Mantas, J. (IOS Press, 2014)
This volume focuses on the activities on Health Telematics Education. In Europe, coordinated activities in healthcare informatics education started in the late 1980's with the establisment of European Courses in Health Teematics. At the same time the European Commission foresaw the need for spreading the knowledge of IT in the Healthcare Sector. Therefore the EC, since then, have supported the initiatives that aim to create awareness, stimulate diffusion, educate and train the users (healthcare professionals) in the application of Information Technology to the Healthcare Sector. Such an initiative is the NIGHTINGALE project which is an essential project in the planning and implementation of strategy timing the Nursing profession in using and applying healthcare information sytems, as well as, the IT EDUCTRA project which covers a more wide spectrum of the Health Telematics Education. The objective of this book is to promote the appropriate use of the developed Telematics infrastructure across Europe by educating and training healthcare professionals in a harmonising way across Europe in the upcoming field of Health and Nursing Informatics. For achieving this objective the European Commission established a series of European Conferences on Health Telematics Education, and Workshops by experts (users, developers and policymakers). In this book the Proceedings of the first European Conference in 'Health Telematics Education' (HTE'96), organised by the NIGHTINGALE project and supported by the IT EDUCTRA project, are included as well as the minutes and the presentations of the NIGHTINGALE Workshops.